Internationalization of higher education and the impacts on academic faculty members. (June 2015) - Bedenlier, Svenja; Zawacki-Richter, Olaf
Research on internationalization processes in higher education has steadily increased over the past decades. However, there is still a lack of analysis of how these developments have affected higher education and, specifically, the group of academic faculty members. To close this gap, this study explores the effects of internationalization on this stakeholder group. A two-round mixed-methods approach was applied in order to identify impacts on this group and rate their importance. From the internationally composed expert panel's responses, 25 impacts on the individual, institutional, and global level were derived, constituting a preliminary foundation for further research on this topic. Findings from the study indicate a need for further investigation of the nature of individual impacts, as well as discussion on the separation of globalization and internationalization in higher education. Furthermore, they demonstrate the necessity of conducting research differentiated according to higher education systems and the faculty members within.